Pengembangan Sistem Pemantauan dan Pengendalian Jarak Jauh Berbasis IoT pada Penerangan Jalan Permukiman - Ichsan Wasiso; Andriyan Dwi Putra; Arif Nur Rohman (KLIK: Kajian Ilmiah Informatika dan Komputer, 2024)
Street lighting in residential areas, mainly rural or suburban areas, is vital in improving public safety, comfort, and security. However, many existing lighting systems still need to be more efficient, with high energy consumption and manual monitoring. This causes delays in repairs when damage or disruption occurs. This study aims to develop a Remote Monitoring and Control System for Street Lighting (SITERANG) based on the Internet of Things (IoT) to overcome these problems. The SITERANG system allows real-time and centralized monitoring of street lighting conditions. It offers energy-saving solutions through lighting intensity settings that can be adjusted according to needs, such as at night when community activity is reduced. SITERANG has lighting asset management features, automatic ON/OFF control, and a centralized monitoring system, allowing efficient energy consumption and cost analysis. The test results show that this system has been proven to save energy consumption by up to 49.17% compared to conventional lighting systems, directly reducing operational costs and electricity bills. The implementation of SITERANG offers a sustainable and efficient solution, providing significant energy savings and facilitating the maintenance of street lighting infrastructure in densely populated residential areas.